Słowotwórstwo nazwisk mieszkańców wsi we wrzesińskich księgach chrztu z XVIII wieku - Sieradzki, Andrzej (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The article studies name derivatives referring to rural population recorded in the eighteenth-century baptismal books of Września. The core of the study are 164 surnames formed by the addition of the suffixes -ski, -ewicz, -owicz as well as the basic -k-. The studies completed demonstrate that in the process of creation of names, over the entire 18th century, the most dominating were the word formation models with suffixes including the basic -k-. Within this category the suffix -ak was the most active element. Of marginal importance (only in the creation of formal derivatives) was the suffix -ski and the derived suffixes. Only 20 formations were created with their use during the whole century. On the basis of the analysis of the documents, it can be assumed that in the rural area near Września there were no word-formative models with the formatives -ewicz and -owicz. The attested surnames (7), recorded between 1753 and 1760, must have been brought from other areas.